Definition membership function based on approach to hedge algebras - VanThang, Doan; Van Ban, Doan (Journal of Computer Science and Cybernetics, 2016)
In this paper, we describe a hedge algebras based approach to modeling uncertainty in fuzzy object-oriented databases. Membership value reflects the degree of fuzziness existing in the data value and uncertainty is extended to the class definition level and is the basis for the determination of the membership of an object in a class. On this basis, we recommend methods of determining the membership degree on characteristics of fuzzy attributes, object/class, class/superclass and in addition, multiple inheritance was discussed and analyzed.